Implementasi Perda Kota Jambi Nomor 5 Tahun 2024 Tentang Rancangan Tata Ruang Wilayah Kota Jambi Tahun 2024-2044 - Sapitri, Wahyuni; Kurniasih, Lara; Salsabila, Viyosi; Hazariga, Adam (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the implementation of Jambi City Regional Regulation Number 5 of 2024 concerning the Spatial Planning (RTRW) of Jambi City for the period 2024–2044, particularly in relation to the use of public road space by informal economic actors, specifically street vendors (PKL). Employing a normative-empirical legal method with a qualitative approach through field observation and interviews, this research identifies a significant discrepancy between the planned spatial framework outlined in the RTRW and the actual use of public space by the community. The findings reveal that the occupation of road shoulders for informal trade has exceeded the designated function of primary collector roads as regulated in Article 21 paragraph (3) of the RTRW, and does not fully align with spatial zoning principles under relevant sectoral laws, including technical guidelines as per Ministry of Public Works Regulation Number 5 of 2023. Such inconsistencies have led to traffic congestion, urban aesthetic degradation, and potential horizontal conflicts between informal and formal economic actors. The study further evaluates the regulation within the framework of legislative drafting principles under Law Number 13 of 2022, concluding that its implementation has not yet achieved full sociological enforceability. As a recommendation, the study calls for the enactment of derivative regulations in the form of a Mayor Regulation (Peraturan Wali Kota) to govern technical aspects of spatial usage for informal economic activities, and the formal designation of city squares (alun-alun) as strategic zones to ensure legality, spatial order, and distributive justice.